The Effect Of Leadership Style, Workload, and Career Level On the Performance Of Upt Employees Galang Puskesmas - Yendri, Yendri; W, Diana Titik (Zona Manajerial: Program Studi Manajemen (S1), 2021)
The purpose of this study was to analyze the effect of leadership style, workload, and career advancement on the performance of UPT employees. Galang Health Center. The dependent variable in this study is employee performance (Y). Meanwhile, the independent variables are Leadership Style (X1), Workload (X2) and Career Path (X3). the population used in this study were UPT employees. Batam City Health Center. 60 employees used saturated sampling technique and obtained a sample of 60 respondents. Multiple linear regression analysis method using SPSS 25.0 program. The results showed that there were variables that had a significant positive and insignificant negative effect on the performance of UPT employees. Batam City Health Center. The value of R Square on the variables of Leadership Style, Workload and Career Path affects performance by 80.4%.